2018
DOI: 10.1155/2018/3481806
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Decontamination of Onion by Corona Discharge Air Plasma during Cold Storage

Abstract: Corona discharge air plasma (CDAP) is a nonthermal decontamination technology which is generating antimicrobial agents such as photons, electrons, positively and negatively charged ions, atoms, and free radicals. We investigated the effect of a corona discharge under atmospheric pressure on the sterilization of postharvest fungal pathogens on onion. The main antimicrobial reactive substance generated by CDAP was O3. The active species such as nitric oxide (NO) and nitric dioxide (NO2) were nearly detected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Similar results were obtained by Chang et al [ 46 ] where they tested a different plasma treatment, namely corona discharge air plasma (CDAP), which consists of nitric oxide and nitric dioxide, on the decontaminating microbes on onion. They found that the isolation frequency of Fusarium spp.…”
Section: Resultssupporting
confidence: 83%
“…Similar results were obtained by Chang et al [ 46 ] where they tested a different plasma treatment, namely corona discharge air plasma (CDAP), which consists of nitric oxide and nitric dioxide, on the decontaminating microbes on onion. They found that the isolation frequency of Fusarium spp.…”
Section: Resultssupporting
confidence: 83%
“…Hence, there are different areas of their potential application. Recently reported plasmas [18][19][20][21][22][23][24] resemble LPGP neither in the methods of their generation nor in their character.…”
Section: Introductionmentioning
confidence: 99%
“…Corona discharge, with its low cost and ease of operation, has been applied in microbial purification, surface treatment, and spore inactivation [49]. This technology has demonstrated significant potential in enhancing the quality of agricultural products, including onions [51], tomatoes [52] and kumquat fruits [53]. Additionally, both DC and pulsed corona discharges have shown effectiveness against Streptococci biofilms and B. cereus spores on plastic surfaces [54].…”
Section: Corona Dischargementioning
confidence: 99%